Investigating vertical charge plasma tunnel field effect transistors beyond semiclassical assumptions - Iman Chahardah Cherik; Saeed Mohammadi; Paul K. Hurley; Lida Ansari; Farzan Gity (Scientific Reports)
Abstract In this paper, we examine the effects of subband quantization on the efficacy of an L-shaped gate vertical dopingless tunneling field-effect transistor. The proposed architecture leverages an intrinsic tunneling interface that is fully aligned with the gate metal, resulting in enhanced electrostatic control. We utilized a two-step numerical simulation approach grounded in the Schrödinger-Poisson equations to evaluate the performance of our proposed device and accurately calculate the ON-state current. Additionally, we assessed the influence of defects at the heterojunction on the performance of our device. Under quantum mechanical assumptions, parameters such as I ON = 23.8 µA/µm, SS AVG = 12.03 mV/dec, and the I ON/I OFF ratio = 4.88 × 1010 indicate that our structure is a promising candidate for high-performance applications.